Review of the Cambrian volcanic activity in Morocco: geochemical fingerprints and geotectonic implications for the rifting of West Gondwana - Pouclet, André; El Hadi, Hassan; Álvaro, J. Javier; Bardintzeff, Jacques-Marie; Benharref, Mohammed; Fekkak, Abdelilah (International journal of earth sciences : Geologische Rundschau, 2018)
Volcanic activities related to the opening of a Cambrian rift in Morocco were widespread from the Fortunian to the Cambrian Epoch 3. Numerous data are available from northwestern volcanic sites, particularly in the western High Atlas, but they are scarce from the southeastern sites. New data are documented here from the volcanic formations exposed in the Jbel Tazoult n’Ouzina of the Tafilalt Province, eastern Anti-Atlas and dated to Cambrian Epoch 2–3. The Cambrian volcanic activities recorded in the High Atlas, Anti-Atlas, and Coastal Meseta are synthesized to refine their stratigraphic setting and to characterize their magmatic affinities and fingerprints. Six volcanic pulses are determined as tholeiitic, transitional, and alkaline suites. The tholeiitic and transitional magmas originated from primitive mantle and E-MORB-type sources with a spinel- and garnet-bearing lherzolite composition. Some of them were modified by assimilation–fractional crystallisation processes during crust–mantle interactions. The alkaline magmas fit with an OIB-type and a garnet-bearing lherzolite source. The palaeogeographic distribution of the magmatic suites was controlled by the lithospheric thinning of the Cambrian Atlas Rift and lithospheric constraints of the Pan-African metacraton and West African craton.